Body proportions, body composition and pubertal development of children in competitive sports - Damsgaard, R.; Bencke, J.; Matthiesen, G.; Petersen, J. H.; Muller, J. (Scandinavian Journal of Medicine & Science in Sports, 2001)
The aim of this study was primarily to investigate anthropometric variables, body composition and pubertal development in children aged 9-13 participating in competitive sports. Secondly, the influence of age, sport, training hours and pubertal development/maternal menarcheal age on body composition and pubertal development was explored. A total of 183 (96 girls, 87 boys) children performing swimming (Sw), tennis (Te), European team handball (TH), and gymnastics (Gy) took part in the study. Anthropometric measurements and pubertal development were determined. The participants completed a questionnaire regarding hours of training per week and maternal menarcheal age. Significant differences in stature (z-scores) were found in both boys (Sw=0.06; Te=0.04; TH=0.05; Gy=-0.66, P<0.004) and girls (Sw=0.12; Te=0.19; TH=0.25; Gy=-0.96, P<0.004). In girls, sum of skinfolds in millimetres (Sw=33.4; Te=33.3; TH=41.0; Gy=27.2, P<0.02) and body mass index z-scores (SW=0.00; Te=-0.27; TH=0.35; Gy=-0.25, P<0.001) were different between the sports. A regression analysis revealed that in girls, age and maternal menarcheal age were significantly associated with pubertal development (P<0.005 and P<0.01), respectively, and sport was associated with the sum of skinfolds (P<0.05). In boys, only age was significantly associated with pubertal development (P<0.005). In conclusion, anthropometric and body composition differences exist in athletes of both sexes from different sports but are more evident in females. Most importantly, we did not find any effect of training on body composition or pubertal development, confirming previous data that children in competitive sports are selected due to constitutional factors.